A reinforcing protection for steel parking-structure column under vehicular impact and design method. (February 2023) - He, Yongjun; Xiang, Siyu; Zhou, Xuhong
Abstract: Previous studies manifest that steel parking-structure columns have an inferior impact resistance. The main objective of this research is to present and design a reinforcing protection (RP) for the existing columns to prevent structural damage under vehicular impacts. The failure modes of the parking-structure column were disclosed based on the validated numerical methods and reduced vehicle model. According to the failure modes, a novel RP was proposed which has the virtues of easily assembling and without taking extra land. Subsequently, numerical analyses were conducted to explore the behaviour of the column equipped with an RP. The results demonstrate that the RP is effective at reducing lateral deformation, particularly local deformation. More significantly, they show that diverse RPs will cause the reinforcing columns to exhibit various failure modes wherein failure mode II where two plastic hinges appear at the column middle is an expected pattern for the ideal design. To better design the RP, the analytical study was carried out to describe the relationship of PR's sectional parameter and then a procedure was given for a rapid optimal design. Eventually, the well-designed RPs were applied to the different columns and their universality and effectiveness were validated. The RP with a good design can efficiently and feasibly improve the impact resistance of the existing column, which can be utilized and promoted in the steel parking structure. Highlights: An innovative reinforcing protection (RP) for the steel column under impact is proposed. Three different failure modes of reinforcing columns under collisions are determined. Relationships are given of RP's parameters to make reinforcing columns reach ideal failure mode. Analytical procedures are provided for optimally designing RP.